MENINGKATKAN PEMAHAMAN BANK SAMPAH DAN KOMPOSTING DENGAN MEDIA POSTER BAGI SISWA - Sucahyanto, Sucahyanto; Aris, Munandar; Yasmine, Racmadiena Aulia (Peneliti.net, 2023)
Damage to the environment that often occurs in the environment is a waste bank and improper composting. There needs to be encouragement for the younger generation in managing waste properly. Managing waste properly can be applied in schools. This study aims to increase students' understanding of bank waste and composting and to determine the effectiveness of a media in increasing understanding of bank waste and composting. In increasing understanding of bank waste and composting media posters are used as a means of information guidance. The research location is at SMA Negeri 42 Jakarta. The research population is all students with a research sample of 90 students. The sampling technique uses probability sampling technique. The method used is quantitative descriptive research. This research uses pretest and posttest. The data analysis technique presented is the mean and the N-Gain Score to determine the increase in students' understanding of waste management, and to see the effectiveness of the poster media used. From the results of calculating the average pretest and posttest values, it can be interpreted that there has been an increase in understanding of bank waste and composting using poster media. The average pretest score was 61.2 and the posttest average score was 88.9. The difference between the pretest and posttest scores is 27.7 points. From the table of N-Gain test results, it can be concluded that the waste bank and composting poster media in the interpretation category is quite effective with an average value obtained of 71.04% where this value is included in the quite effective category with a percentage of 56% - 75%.